Protection of Workers in the Implementationof the Principle of Human Rights Citizens in Indonesia - Suci Ramadani (International Conference of ASEAN Prespective and Policy (ICAP), 2018)
Protection of workers in Indonesia is regulated through the provisions of Law no. 13 Year 2003 on Manpower. This provides for general provisions on the rights and obligations of workers and employers. Special arrangements are not only governed by the Ministry of Manpower, the local government regulates the policy of the Regional Regulation, so in providing protection for local workers it is necessary to develop the principles of City of Human Rights. Limitations of discussion are reviewed as follows how the law regulation of protection of workers in Indonesia? How to regulate the principles of the City of Human Rights in Indonesia? how to protect workers in the application of the principles of the City of Human Rights in Indonesia? The research method used is normative juridical using secondary data that is labor regulation and human rights regulation in accordance with research study. Human rights cities are human rights approaches to local governance including democratic principles, participation, responsible leadership, transparency, accountability, non-discrimination, empowerment and rule of law. That the protection of workers is a protection of human rights as regulated in the 1945 Constitution, the Law on Human Rights, so that a national human rights policy action plan that is implemented by the central government and local government through the implementation of the principles of Human Rights City in Indonesia with carrying the 3 pillars of respecting, protecting and fulfilling human rights specifically human rights workers in obtaining basic rights namely the right to obtain employment, protection at work and experiencing termination of employment that can be fulfilled by the local government through the Regional Regulation which is the application of the principle of the City of Rights Human Rights. Protection of workers within the Local Regulation to incorporate the principles of City of Human Rights that the protection of workers is a principle of human rights that must be implemented in the region.